2014
DOI: 10.1063/1.4868295
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure sintering behavior of α″-Fe16N2 nanopowder

Abstract: α″-Fe16N2 nanopowder was sintered at high-pressure and low temperature in order to explore its feasibility as a bulk magnet. TEM observation confirmed that the nanopowder was densely consolidated by sintering at a pressure of 1.2 GPa and temperatures around 200 °C. Increasing the sintering temperature enhanced the densification, leading to a suppression of oxidization. However, XRD analysis revealed that sintering at 222 °C caused the decomposition α″ → α-Fe + ε-Fe3N, which reduced the saturated magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Similar diffraction line broadening has been reported for oxides, nitrides and carbides, where the grain size was reduced to the nanometer scale under microstructural strain [13,23,24]. The electron diffraction shown in Fig.…”
Section: Characterizationsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar diffraction line broadening has been reported for oxides, nitrides and carbides, where the grain size was reduced to the nanometer scale under microstructural strain [13,23,24]. The electron diffraction shown in Fig.…”
Section: Characterizationsupporting
confidence: 56%
“…The synthesis and sintering of metal nitrides have been examined on optical, magnetic, electronic and refractory materials, such as GaN, FeN x , BN, and AlN [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, higher-than-Fe magnetic moment for α ′′ − Fe 16 N 2 2 and Fe 4 N 3,4 ), has been the driving force for the intense research work in carried out in the Fe-N system. 5,6 Though former is a heavily debated compound, 7 the origin of high magnetic moment in tetra metal nitrides (M 4 N) is relatively well-understood. In M 4 N enhanced magnetic moment is caused by a volume expansion (compared to a hypothetical fcc metal).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the a 00 -Fe 16 N 2 phase decomposed into g 0 -Fe 4 N þ Fe. Some groups have found that the a 00 -Fe 16 N 2 decomposes into an e-Fe 3 N phase, [15] which may be because their sample was prepared by an ammonia reaction approach. [15] The results suggest that the ball-milling sample is different from the chemical-reaction sample in terms of the decomposition process and products formed.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…[5,[7][8][9][10][11] a 00 -Fe 16 N 2 thin film with high Ms has potential applications in the magnetic recording field. Besides the thin film investigation, many groups are working on a 00 -Fe 16 N 2 powder preparation, [12][13][14][15][16] which could be used for permanent magnet preparation. This is the so-called "bottom-up" approach, [17,18] in which the a 00 -Fe 16 N 2 powder is first synthesized and then compressed into the required shape.…”
Section: Introductionmentioning
confidence: 99%